Science-technology-innovation policies: Cuban experiences for development of biotechnology - Ca, Tran Ngoc; Anh, Nguyen Hong; Ha, Chu Thi Thu; Bach, Tran Xuan; Long, Luu Hoang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
This paper deals with the relation between the development of biotechnology and science-technology innovation policies in Cuba as well as decision-making mechanisms. This shows the impacts from certain policies to development of biotechnology sector, especially in health care fields. The challenges Cuba has to face in biotechnology sector and science-technology-innovation policies as well as lessons from concrete cases may be found useful for Vietnam in process of making and implementing science-technology-innovation policies in present and future times. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> Code: 20030201